Imaginary Perspective Taking in Six-Year-Olds - Barbara Bilewicz-Kuźnia (Nicolaus Copernicus University in Toruń, 2020)
The study concerns imaginary perspective taking (IPT) in six-year-olds and is a replica of the studies undertaken by the Van den Heuvel-Panhuizen, Elia and Robitzsch team 2015). Imaginary perspective taking comprises two components: IPT 1 refers to perception, the socalled "visibility of objects", i.e. deducing which object is visible or not from different points of view. IPT 2 (appearance, imaginary perspective taking) refers to the ability to describe what an object looks like when viewed from different points of view. The study was aimed at defining development of the six-year-olds' ability to take a different perspective and comparing it with the results of Van den Heuvel-Panhuizen's team. 74 Polish six-year-olds participated in the study: 36 children living in the urban environment (17 girls, 19 boys) and 38 children from rural areas (15 girls and 23 boys). A set of trials of Imaginary Perspective Items IPT1 Visibility items and IPT2 Appearance items constituted the research tool. The studies have shown that Polish six-year-olds demonstrate the first level of competence in taking a different perspective and a high ability to understand that different locations mean different points of view. The vast majority (71.8%) of children correctly determine whether an object is seen or not from a different perspective. The ability to properly perceive the appearance and shape of an object is at the development stage in the examined six-year-olds (45.5% of the tasks performed correctly). The study confirmed the conclusions drawn from the reports of Van den Heuvel-Panhuizen, Elia and Robitzsch (2015) and proved that neither gender nor local environment constitute factors differentiating six-year-olds' achievements in developing the ability to take a different perspective